Pre-literacy 12-24 months: what behaviors demonstrate engagement and what strategies support increased engagement? - Elmhorst, Megan (My University, 2012)
When adults indulge in a good book, it is because it captures his or her interest in some shape or form. The same is true for 12-24 month-olds. A book may capture the interest of a child for a particular reason. When this interest occurs, parents become an essential piece in the engagement puzzle. They have a choice to acknowledge engagement and extend it using various strategies or to let the moment pass. This action research studied the engagement behaviors of 12-24 month-olds in the pre-literacy phases of reading and the strategies that support increased engagement. The study involved four children ranging between the ages of 12-24 months. They were recorded reading with a parent during two different sessions. Parents were also interviewed before and after the study to get a better understanding of the nature of reading experiences they had with their children and to see if parents learned anything new about their children and how to engage them while reading together. The Developmental Continuum for Reading: Pre-Verbal Phase (Engagement) was utilized to give an idea for what the children were already demonstrating and to provide a focus for where they needed support to increase engagement. A focus group was also conducted to gain insight into reading and engagement through a parent's eyes. Results indicated that parents need to be aware of engagement behaviors and strategies in order to support increased engagement in their 12-24 month-olds.
Plan B Paper. 2012. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 47 leaves. Includes bibliographical references (leaves 34-37).
Keywords: Infants--Books and reading; Literacy; Reading